Parkour-Based Activities in the Athletic Development of Youth Basketball Players - Williams, Mark David; Strafford, Ben William; Stone, Joseph Antony; Moran, Jason (Frontiers in Physiology, 2021)
While ideas from long-term athlete development (LTAD) models have been adopted and integrated across different sports, issues related to early specialization, such as increased risk of injury and burnout, are still common. Although some benefits may be associated with early sport specialization, sports sampling is purported to be a more effective approach to the long-term health and wellbeing of children. Furthermore, the concept of developing what are commonly referred to as ‘fundamental movement skills’ (FMS) is central to the rationale for delaying single sports specialization. However, in place of sports sampling, it appears that the practice of strength and conditioning (S&C) has become a driving force behind developmental models for youth athletes, highlighted by the growing body of literature regarding youth athletic development training. In this perspective piece, we explore how conventional S&C practice may insufficiently develop FMS because typically, it only emphasizes a narrow range of foundational exercises that serve a limited role towards the development of action capabilities in youth athletic populations. We further discuss how this approach may limit the transferability of physical qualities, such as muscular strength, to sports-specific tasks. Through an of ecological dynamics lens, and using basketball as an example, we explore the potential for parkour-based activity within the LTAD of youth basketball players. We propose parkour as a training modality to not only encourage movement diversity and adaptability, but also as part of an advanced strength training strategy for the transfer of conventional S&C training.